Multilevel Analysis on the Bio-psychosocial and Environment Factors Affecting the Risk of Pneumonia in Infants - Astri Yunita; Bhisma Murti; Yulia Lanti Retno Dewi (Masters Program in Public Health, 2016)
Background: Pneumonia is an illness of the maincauses of pain and death in toddler in the world. The incidence of pneumonia in Indonesia has increased, from 2007 about 2.1% and in 2013 about2.7%. Pneumonia in toddler in Indonesia is an issue that is important to do the actions of prevention and control of pneumonia. This study was aimed to investigate the factors biopsychosocial to the risk of pneumonia in toddlers.Subjects and Method: This was an analytical observational study with case control design, carried out on 2 August to 16 September 2016. A total of 140 subjects in Banjarnegara, Central Java, were selected by fixed disease sampling. The dependent was pneumonia in infants. The independent variables were exposure to CO, H2S, family income, maternal education, household smoke exposure, sanitary home, chain-smoking family activity, anxiety. The data was collected by using a questionnaire, check list and recording and analyzed by using Logistic regression.Results: There was influence of exposure of CO (OR= 1.46; 95% CI= 0.17 to 21; p= 0.970), H2S (OR= 0.53; 95% CI= 0.98 to 2.92; p= 0.412), family income (OR= 1.90; 95% CI= 0.78 to 4.65; p= 0.365), maternal education (OR= 1.75; 95% CI= 0.72 to 4.25; p= 0.474), household smoke exposure (OR= 5.63; 95% CI= 2.27 to 13.95; p= 0.001), home sanitation (OR= 6.23; 95% CI= 2.61 to 14.84; p=0.001), smoking activity (OR= 3.19; 95% CI= 1.33 to 7.66; p= 0.020) and the incidence of pneumonia toddlers. There was the influence of anxiety to pneumonia in toddler (OR= 16; 96% CI= 6.87 to 37.75; p< 0.001). There was the influence of contextual conditions to pneumonia in toddler (ICC = 36.97%; role of thumb 5 to 8% likelihood ratio p= 0.008; 95% CI= 0.45 to 8.17).Conclusion: There is the influence of exposure to CO, H2S, family income, maternal education, household smoke exposure, home sanitation, smoking activity. There is the influence of anxiety of pneumonia in toddler. The condition has influence contextual variations toddler pneumonia incident, so it is noteworthy.Keywords: bio-psychosocial, environmental factor, pneumonia toddlersCorrespondence: Astri Yunita. Masters Program in Public Health, SebelasMaret University, Surakarta. Email: astriyunita07@yahoo.co.id. Mobile: +6285641797995Journal of Epidemiology and Public Health (2016), 1(1): 1-10https://doi.org/10.26911/jepublichealth.2016.01.01.01